2020
DOI: 10.1002/ange.201915848
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Modulation of the Zr MOF UiO‐66 for Defect‐Controlled Combination Anticancer Drug Delivery

Abstract: Metal–organic frameworks (MOFs) are emerging as leading candidates for nanoscale drug delivery, as a consequence of their high drug capacities, ease of functionality, and the ability to carefully engineer key physical properties. Despite many anticancer treatment regimens consisting of a cocktail of different drugs, examples of delivery of multiple drugs from one MOF are rare, potentially hampered by difficulties in postsynthetic loading of more than one cargo molecule. Herein, we report a new strategy, multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 56 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…Several studies suggest that MOFs of various types show great promise in drug delivery of, e.g. anticancer, anti-inflammatory, and antibacterial agents (Dong et al, 2018;Li et al, 2019b;Nasrabadi et al, 2019;Ab anades L azaro et al, 2020;Lu et al, 2020). An important and unique feature of MOFs as carriers is their low toxicity and their enhancement of bioavailability and solubility of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that MOFs of various types show great promise in drug delivery of, e.g. anticancer, anti-inflammatory, and antibacterial agents (Dong et al, 2018;Li et al, 2019b;Nasrabadi et al, 2019;Ab anades L azaro et al, 2020;Lu et al, 2020). An important and unique feature of MOFs as carriers is their low toxicity and their enhancement of bioavailability and solubility of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Of the numerous metal–organic frameworks with potential use as drug delivery systems, Zn-, Fe-, Zr-, and Mg-based metal–organic frameworks are being researched intensely due to their low cytotoxicity, high biodegradability, and high biocompatibility. 7 , 10 , 12 16 Among the numerous groups of possible MOFs with various topologies, the zirconium-based metal–organic framework UiO-66 (Universitetet i Oslo) composed of octahedron clusters [Zr 6 O 4 (OH) 4 ] and 1,4-benzenedicarboxylic acid ligands meets the requirements for drug carriers. Due to its properties, such as high thermal and physical properties, high surface area, and a high degree of freedom in synthesis and postsynthesis, its potential for modification has attracted considerable attention in terms of its potential as a drug delivery carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its properties, such as high thermal and physical properties, high surface area, and a high degree of freedom in synthesis and postsynthesis, its potential for modification has attracted considerable attention in terms of its potential as a drug delivery carrier. 12 15 In the work by Jarai et al, 13 composite dexamethasone@UiO-66 and rhodamien@UiO-66 were determined as novel drug delivery systems for pulmonary diseases. It was found that the modulated synthesis of 100 nm crystals of UiO-66 does not affect the aerodynamics of NPs in aerosols and has a negligible effect on drug loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As porous nanomaterials, MOFs are capable of high loading capacities, controlled release, plasticity, and biosafety, which facilitate the selective transportation of nanomaterials through the porous network (An et al, 2012). MOFs have been proposed as an attractive alternative to mitigate drawbacks that other drug delivery systems (DDSs) face (Abanades Lazaro et al, 2020). Thus, MOFs have already served as a successful drug delivery platform (Zhao et al, 2011).…”
mentioning
confidence: 99%